2018
DOI: 10.1016/j.ijdevneu.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Background cortisol versus social anxiety as correlates of HPA‐axis recovery from stress in boys with Autism Spectrum Disorder

Abstract: Children with Autism Spectrum Disorder (ASD) show dysregulation of the expected Hypothalamus-Pituitary-Adrenal (HPA) axis and elevated cortisol responses to stress and response patterns, but little has been reported regarding their recovery from stress in terms of cortisol concentrations. This response was investigated in a sample of 32 young males with ASD aged between 9 and 18 years (M = 14.3 yr, SD = 2.7 yr), using a standardised experimental protocol combined with individualised stressor and non-stressor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…There is a large body of evidence suggesting global disruptions to cortisol signaling in autism (95,(185)(186)(187)(188)(189)(190)(191)(192)(193) and independent studies have reported HPA hyperactivation (185,188,194,195) and increased stress reactivity (186,196) in ASC. A relationship between elevated evening cortisol and psychopathology in ASC has been proposed (194); altered cortisol responses were associated with GAD and social anxiety in boys with ASC (197,198), while the cortisol awakening response was reported to correlate with depression and suicidal ideation in autistic girls (199). Moreover, targeted molecular studies have found disruptions to GR expression in ASC brain tissue (200), while genetic polymorphisms in the GR chaperone were associated with serum cortisol levels (201) and moderated the relationship between autistic traits and social anxiety (202).…”
Section: Figurementioning
confidence: 99%
“…There is a large body of evidence suggesting global disruptions to cortisol signaling in autism (95,(185)(186)(187)(188)(189)(190)(191)(192)(193) and independent studies have reported HPA hyperactivation (185,188,194,195) and increased stress reactivity (186,196) in ASC. A relationship between elevated evening cortisol and psychopathology in ASC has been proposed (194); altered cortisol responses were associated with GAD and social anxiety in boys with ASC (197,198), while the cortisol awakening response was reported to correlate with depression and suicidal ideation in autistic girls (199). Moreover, targeted molecular studies have found disruptions to GR expression in ASC brain tissue (200), while genetic polymorphisms in the GR chaperone were associated with serum cortisol levels (201) and moderated the relationship between autistic traits and social anxiety (202).…”
Section: Figurementioning
confidence: 99%
“…On the other hand, core symptoms of ASD, such as sensory deficits, may contribute to stress system dysregulation ( Kushki et al, 2013 ). Moreover, alterations in the regulation of stress system components may account at least partially for several comorbid conditions that often accompany ASD, such as depression and anxiety disorders amongst others ( Hollocks et al, 2014 ; Bitsika et al, 2015 , 2018 ; Sharpley et al, 2016 ; Muscatello et al, 2021 ). In fact, excessive and prolonged activation of the stress system might lead to increased and prolonged production of stress system mediators, such as corticotropin-releasing hormone (CRH), cortisol, and catecholamines, which could explain many of the long-term psychopathological complications of chronic stress ( Agorastos et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…• Dysfunction of the thyroid gland and delayed development of a child [2][3][4] • Thyroid function in mothers of children with ASD, with women diagnosed with hypothyroidism giving birth to children who quite often, at the age of 14 months, showed signs of autism with impaired intelligence and delayed cognitive development [5,6] • Imbalance in the level of steroid hormones, especially cortisol, in children with ASD compared with neurotypical children [7] • Imbalance in the levels of testosterone and oxytocin in children with ASD compared to neurotypical children [8] • Comparative studies of cortisol, melatonin, and oxytocin levels in neurotypical children and in children with ASD, confirming the frequent imbalance in the levels of these hormones in children with ASD [9].…”
Section: Introductionmentioning
confidence: 99%